Synergistic Interface‐Assisted Electrode–Electrolyte Coupling Toward Advanced Charge Storage. Issue 43 (21st September 2020) - Sun, Shuo; Rao, Dewei; Zhai, Teng; Liu, Qi; Huang, Hao; Liu, Bo; Zhang, Hongshen; Xue, Liang; Xia, Hui
Abstract: Owing to the limited charge storage capability of transitional metal oxides in aqueous electrolytes, the use of redox electrolytes (RE) represents a promising strategy to further increase the energy density of aqueous batteries or pseudocapacitors. The usual coupling of an electrode and an RE possesses weak electrode/RE interaction and weak adsorption of redox moieties on the electrode, resulting in a low capacity contribution and fast self‐discharge. In this work, Fe(CN)6 4− groups are grafted on the surface of Co3 O4 electrode via formation of CoN bonds, creating a synergistic interface between the electrode and the RE. With such an interface, the coupled Co3 O4 –RE system exhibits greatly enhanced charge storage from both Co3 O4 and RE, delivering a large reversible capacity of ≈1000 mC cm −2 together with greatly reduced self‐discharge. The significantly improved electrochemical activity of Co3 O4 can be attributed to the tuned work function via charge injection from Fe(CN)6 4−, while the greatly enhanced adsorption of K3 Fe(CN)6 molecules is achieved by the interface induced dipole–dipole interaction on the liquid side. Furthermore, this enhanced electrode–electrolyte coupling is also applicable in the NiO–RE system, demonstrating that the synergistic interface design can be a general strategy to integrate electrode and electrolyte for high‐performance energy storage devices. Abstract : A "smart" Co3 O4 –redox electrolyte (RE) interface that not only significantly increases the electrochemical activity of Co3 O4 but also effectively confines the redox species is created, thus simultaneously achieving remarkable enhancement of faradaic charge storage capability and suppressed self‐discharge. With such a synergistic interface, the energy density of RE‐enhanced aqueous rechargeable batteries can be effectively increased without compromising the low self‐discharge.